2009
DOI: 10.1149/1.3148327
|View full text |Cite
|
Sign up to set email alerts
|

Coloration Mechanism in Proton-Intercalated Electrochromic Hydrated NiO[sub y] and Ni[sub 1−x]V[sub x]O[sub y] Thin Films

Abstract: Electrochromic ͑EC͒ films of nickel oxide, with and without vanadium, were prepared by reactive dc magnetron sputtering. They were characterized by electrochemical and optical measurements and studied by X-ray photoelectron spectroscopy ͑PES͒ using synchrotron radiation. The films were analyzed under as-deposited conditions and after bleaching/coloration by insertion/ extraction of protons from a basic solution and ensuing charge stabilization. Optical measurements were consistent with a coloration process due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…By examining the carbonate contribution to C1 at 289 eV by XPS it was concluded that about 10% of the oxygen was bound to carbon. The films are probably not pure NiO z , but also contain hydroxide phases, as shown by Avendano et al [16]. NiO z was compatible with all three electrolytes.…”
Section: Tungsten Oxidementioning
confidence: 55%
“…By examining the carbonate contribution to C1 at 289 eV by XPS it was concluded that about 10% of the oxygen was bound to carbon. The films are probably not pure NiO z , but also contain hydroxide phases, as shown by Avendano et al [16]. NiO z was compatible with all three electrolytes.…”
Section: Tungsten Oxidementioning
confidence: 55%
“…Figure 3 displays corresponding cross-sectional views on fractured samples. The latter SEM micrographs give clear evidence for columnar structures and porosity on the nanometer scale; these features are conducive to ionic transport and are hence advantageous with regard to EC performance [1,14]. Film thicknesses for samples on Si were found to be in the approximate thickness range 350 < d < 370 nm.…”
Section: Composition Structure and Morphologymentioning
confidence: 92%
“…Corresponding bulk densities are 7.16 g/cm 3 for monoclinic WO 3 and 6.67 g/cm 3 for NiO single crystals, thus showing that the films have a large amount of porosity. The Ni oxide film, in particular, is expected to be strongly hydrous [14].…”
Section: Composition Structure and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…For nickel oxides the Ni 2p spectra contain multiple peaks at binding energies between about 852 and 870 eV, including the main peak and satellites [20][21][22] NiOOH, since the sample has a darkish brown colour that indicates the presence of some Ni 3+ , which possibly is responsible for the asymmetry of the XPS peaks.…”
Section: Ni 2pmentioning
confidence: 99%